Social emotional learning matters: Interpreting educators’ perspectives at a high-needs rural elementary school - Dyson, Ben; Shen, Yanhua; Howley, Donal; Baek, Seunghyun (Frontiers in Education, 2023)
The purpose of this article was to investigate educators’ experiences and perspectives on implementing Social and Emotional Learning (SEL) in a high-needs rural elementary school setting. Fifteen school educators (n=15), including ten K-5 classroom teachers, one special education teacher, one social worker, and three school leaders, participated in this study. In addition, lessons were observed, and 17 sets of field notes were taken during 17 different days of visit (60-90 minutes) over the two semesters. A case study design drawing on qualitative research methods was utilized. The inductive analysis and constant comparison of the collected data found six themes for the school educators’ prerequisite for academic success, essential skills for everyday life, lack of time, lack of preparation and development, home-school disconnection, and pushback from students. The study provided evidence to support the importance of SEL and revealed nested levels of constraints for school educators’ implementing SEL from the “voices” of school educators.